Influence of Site Factors on the Growth of Chir Pine (Pinus roxburghii Sargent) Forests Along Elevational Gradient - Sharma, D. P.; Malik, Riyaz Ahmad (Indian Forester, 2011)
The investigation was carried out in the Solan Forest Division (900m to 2100m amsl) of Himachal Pradesh to determine the site factors influencing the forest growing stock (FGS) and to develop growth prediction model functions. All site factors i.e. temperature, slope, aspect, soil depth, soil organic carbon, and bulk density were significantly responsible to influence the FGS. The FGS decreased with decrease in temperate along altitudinal gradient from 900 m to 1900 m indicating a positive effect of temperature on the volume of the Forest Growing Stock. The south facing slopes experienced lower FGS as compared to north facing slopes. The gentle slopes had higher FGS as compared to steep slopes. The FGS was also influenced by soil factors which was higher on sites having higher soil depth and soil rich in organic carbon whereas, bulk density showed a reverse trend. Among site factors, the temperature, aspect and soil depth were the major factors that influenced the FGS. The step wise multiple linear regression analysis demonstrated that contribution of the different site factors to the FGS in descending order were as temperature > aspect > soil depth > organic carbon > Bulk density > Slope and among various model functions, the model incorporating temperature, aspect, soil depth and organic carbon were the best fit for the estimation of FGS. Finally, to the scope of future work, the models developed be further tested and validated for a large number of sites.